Characterization of Volatile Oil from Litsea rubicunda - Wan Mohd Nuzul Hakimi Bin W SalleH (Tanjung Malim, 2024)
Characterization of Volatile Oil from Litsea rubicunda by Wan Mohd Nuzul Hakimi Bin W SalleH